Prediksi Tingkat Prevalensi Stunting Kabupaten Lima Puluh Kota Menggunakan Metode Monte Carlo - Mike Zaimy; Sarjon Defit; Gunadi Widi Nurcahyo (Jurnal Informasi dan Teknologi, 2021)
Stunting is a condition of failure to thrive in children under five years old (infants under five years old) due to chronic malnutrition so that children are too short for their age. According to available data, the stunting prevalence rate in Lima Puluh Kota Regency in 2020 is quite high, at 8.28%. This has become the attention of the central government by establishing Lima Puluh Kota Regency as one of the Regencies/Cities Locations for the National Integrated Stunting Reduction Intervention Focus. The results of this study aim to assist the District Government of Lima Puluh Kota in planning the convergence of programs/interventions as an effort to accelerate stunting prevention and reduce the percentage of stunting under five in Lima Puluh Kota Regency. This research data uses the stunting prevalence rate from 2018 to 2020 which comes from data on the number of toddlers and the number of stunting toddlers from 22 health centers in Lima Puluh Kota Regency. Furthermore, the data was processed using the Monte Carlo method to predict the stunting prevalence rate in 2021. Based on the tests conducted using the Monte Carlo method, the highest stunting prediction rates were found at the Pakan Rabaa Public Health Center and the Suliki Public Health Center with a stunting prevalence rate of 11.70%. The level of accuracy obtained is 93.73%. The Monte Carlo method is suitable for predicting the prevalence of stunting in Lima Puluh Kota Regency, seen from the high level of accuracy from the results of data processing.